Analisis Faktor Pendorong Penggunaan Aplikasi Sing! Karaoke by Smule - Ismira Febrina; Ridwan Mustopa; Haryadi Mujianto (Universitas Majalengka, 2022)
This study aims to identify and interpret the factors that encourage audiences to access the Sing! Karaoke by Smule. This research method is qualitative with an interpretative approach. This research was carried out during January 2022 with data collection techniques through interview techniques, literature searches, and interpretation of the data. Interviews were conducted with nine users of the Smule application using several methods, including face-to-face (with health protocols), Video Call, and WhatsApp Chat. The results show that the number of people who access the Smule application cannot be separated from the needs that underlie the users to use it. This is in line with what was stated by Katz, Gurevitch and Haas regarding human needs related to the use of media, namely the existence of cognitive needs, affective needs, personal integrative needs, social integrative needs and the need for escape or tension release.